2017
DOI: 10.1371/journal.pgen.1006904
|View full text |Cite
|
Sign up to set email alerts
|

Tex19.1 promotes Spo11-dependent meiotic recombination in mouse spermatocytes

Abstract: Meiosis relies on the SPO11 endonuclease to generate the recombinogenic DNA double strand breaks (DSBs) required for homologous chromosome synapsis and segregation. The number of meiotic DSBs needs to be sufficient to allow chromosomes to search for and find their homologs, but not excessive to the point of causing genome instability. Here we report that the mammal-specific gene Tex19.1 promotes Spo11-dependent recombination in mouse spermatocytes. We show that the chromosome asynapsis previously reported in T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 58 publications
(152 reference statements)
0
46
0
Order By: Relevance
“…However, mL1-ORF1p immunostaining is elevated approximately two fold in the same cell type in Tex19.1 −/− mice (Figure 1C). Thus, distinct from its role in transcriptional regulation of retrotransposons (Ollinger et al, 2008; Reichmann et al, 2012; Crichton et al, 2017a; Reichmann et al, 2013), Tex19.1 appears to have a role in post-transcriptionally suppressing mL1-ORF1p abundance in meiotic spermatocytes.
10.7554/eLife.26152.003Figure 1.mL1-ORF1p is post-transcriptionally regulated by Tex19.1 in mouse germ cells.( A ) Western blot for mL1-ORF1p in Tex19.1 +/− and Tex19.1 −/− littermate P16 mouse testes. β-actin is a loading control.
…”
Section: Resultsmentioning
confidence: 99%
“…However, mL1-ORF1p immunostaining is elevated approximately two fold in the same cell type in Tex19.1 −/− mice (Figure 1C). Thus, distinct from its role in transcriptional regulation of retrotransposons (Ollinger et al, 2008; Reichmann et al, 2012; Crichton et al, 2017a; Reichmann et al, 2013), Tex19.1 appears to have a role in post-transcriptionally suppressing mL1-ORF1p abundance in meiotic spermatocytes.
10.7554/eLife.26152.003Figure 1.mL1-ORF1p is post-transcriptionally regulated by Tex19.1 in mouse germ cells.( A ) Western blot for mL1-ORF1p in Tex19.1 +/− and Tex19.1 −/− littermate P16 mouse testes. β-actin is a loading control.
…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, SPO11 and SYCP1, markers of meioticspecific double-strand breaks and synapsis, respectively (de Vries et al, 2005;Robert et al, 2016), were expressed in clusters 4-7. TEX19, a regulator of SPO11-dependent meiotic recombination in leptotene (Crichton et al, 2017), was mainly expressed in clusters 3-6. Additionally, OVOL1 and OVOL2, which are localized in the XY body of and human spermatocytes at the pachytene and diplotene stages (Taniguchi et al, 2017), were exclusively highly expressed in clusters 8 and 9.…”
Section: Global Transcriptional Profiling Of Adult Human Testicular Cmentioning
confidence: 99%
“…In addition, during meiosis, interhomolog recombination is initiated by the type II topoisomerase-like activity of the SPO11-TOPVIBL complex, which generates a DNA doublestrand break in one participating chromatid (45)(46)(47)(48). Recent work in mice has demonstrated that the mammalian-specific gene Tex19.1 is required to promote normal levels of these meiotic recombination-initiating events (49). The human ortholog, TEX19, normally has expression restricted to the testis and embryo stem cells, but is also widely activated in cancer cells (31); importantly, this expression is required in a number of distinct cancer cell types to mediate proliferation and cancer stem-like cell self-renewal (50).…”
Section: Activation Of Meiotic Functions In Cancer Cellsmentioning
confidence: 99%